Prevalence and Outcomes of Crohn’s Disease Among Patients Presenting with Lower Abdominal Pain in the Surgical Department - Ahmad Abaidalla; Nasser Mohamed; Salma Mohamed; Majduadeen Alhlafi; Amal Amhawee; Wesam Abraheem (AlQalam Journal of Medical and Applied Sciences, 2025)
Lower abdominal pain is a common clinical complaint and has a wide spectrum of causes, among which is Crohn’s disease (CD). The CD should be diagnosed early to prevent both a late diagnosis and complications in such patients. This study examines the prevalence and clinical consequences of CD in 184 patients with lower abdominal pain who are admitted to Albyeda Medical Center. A retrospective examination identified CD in 6 individuals who were already diagnosed. Of the remainder, 35 were released following negative observation for appendicitis, and 143 had surgery. The histopathological examination of these operations revealed 8 new cases of CD, for a total prevalence of 7.6%. This result emphasizes that in young patients with abdominal pain, CD should be taken into account as one of the possible diagnoses.